2013
DOI: 10.1042/bsr20130079
|View full text |Cite
|
Sign up to set email alerts
|

Malignant H1299 tumour cells preferentially internalize iron-bound inositol hexakisphosphate

Abstract: In colon enterocytes and in well-differentiated colon cancer CaCo-2 cells, InsP6 (inositol hexakisphosphate) inhibits iron uptake by forming extracellular insoluble iron/InsP6 complexes. In this study, we confirmed that CaCo-2 cells are not able to take up iron/InsP6 but, interestingly, found that the cells are able to internalize metal-free and Cr3+-bound InsP6. Thus, the inability of CaCo-2 cells to take up iron/InsP6 complexes seems to be due to the iron-bound state of InsP6. Since recently we demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Further studies from other laboratories have shown that lower concentrations of InsP 6 promoted cell proliferation, while higher concentrations led to induction of apoptosis Helmis et al 2013). Thus, a steady-state distribution of InsPs is the manifestation of a highly dynamic program of production and turnover by Minpp1 and other enzymes that regulate inositol polyphosphate inter-conversion which impact cell survival and death.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies from other laboratories have shown that lower concentrations of InsP 6 promoted cell proliferation, while higher concentrations led to induction of apoptosis Helmis et al 2013). Thus, a steady-state distribution of InsPs is the manifestation of a highly dynamic program of production and turnover by Minpp1 and other enzymes that regulate inositol polyphosphate inter-conversion which impact cell survival and death.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, inositol polyphosphates (InsPs) were shown to play signaling roles in the regulation of calcium mobilization, cell growth, vesicular transport, gene expression, and export of mRNA and apoptosis [30][31][32][33][34]. MINPP1 is an ER luminal soluble protein and dephosphorylates InsPs by removing specifically phosphate group at position 3 and association with apoptosis has been described extensively [17,[35][36][37][38][39][40][41]. MINPP1 is the only ER resident enzyme that can hydrolyze inositol pentakisphosphate and inositol hexakisphosphate and it exhibits characteristics of a stress-responsive molecule during ER stress-induced apoptosis regardless of the underlying involved mechanisms [42].…”
Section: Discussionmentioning
confidence: 99%